A friend to the Sherpas till the end - Abd Razak, Dzulkifli (2008)
DESPITE what he had achieved, he was always very humble and committed." These were the words of the chief administrator of the Hillary Himalayan Trust on learning about the death of the man who conquered Mount Everest in 1953. Sir Edmund P. Hillary, together with Tenzing Norgay, a Sherpa, succeeded at a task seven previous expeditions had failed to achieve. It was not until the death of Norgay that Hillary revealed (in his 1999 book, View From the Summit) that he was about three metres ahead at the final ridge, making him the first person to reach the top of the world's highest mountain at 8,850m. Such was the humility of this heroic figure.